Bridging science, society, and sustainability: The development of SSI-SDGs guidebook for pre-service biology teachers - Ummi Nur Afinni Dwi Jayanti; Kartika Manalu; Yassir Ni'ma Rangga Wiryawan; Neska Fadillah; Rahmania Pamungkas (Universitas Muhammadiyah Malang, 2026)
Background-The need for learning resources that effectively integrate Socio-Scientific Issues (SSI) and the Sustainable Development Goals (SDGs) into biology education underlies the effort to prepare pre-service teachers with 21st-century competencies. Objective-The study aimed to design and develop a guidebook for integrating SSI and SDGs in biology learning that is valid, practical, and effective in improving the pedagogical skills of future biology teachers. Method- The study employed the 4D development model proposed by Thiagarajan and was conducted in 2025 in the Biology Education Program at UIN Sumatera Utara, Medan. The participants were students who had completed the Biology Learning Strategies course and enrolled in Biology Lesson Planning course. Data were collected through questionnaires, document analysis, and expert validation. Results-The findings revealed that both students and lecturers still require a systematic guide for integrating SSI and SDGs effectively into biology instruction. The developed guidebook includes theoretical foundations, applied examples, and contextual learning frameworks designed to foster critical thinking, collaboration, and scientific literacy. Validation results confirmed that the guidebook is feasible, practical, and effective for use in biology education. Conclusion- The guidebook was declared valid, practical and limitedly effective in enhancing pedagogical skills of pre-service biology teachers in planning SSI- and SDG-based instruction.